Ravindranath Tagore rachnavali/ Mera Bachpan - Tagore, Ravindra Nath; Edited by Indra Nath Chaudhury (New Delhi Sasta Sahitya Mandal, 2013)
Novel
Keywords: Hindi novel; Noble prize winner Ravindra Nath Tagore